From scratch : adventures in harvesting, hunting, fishing, and foraging on a fragile planet - Moscow, David, 1974-; Moscow, Jon (New York : Permuted Press, 2022)
"To help us reconnect with the food that sustains our lives, the author has spent four years going around the world and sourcing ingredients within local food ecosystems.
Includes recipes.
Includes index and bibliographic references (pages 282-298).
Keywords: Moscow, David, -- 1974- -- Travel; Gastronomy; Food supply